The Influence of Triad Nations' Environments on Price-Quality Product Strategies and MNC Performance - Brouthers, Lance Eliot; Werner, Steve; Matulich, Erika (Journal of International Business Studies, 2000)
Is there a relationship between home-country competitive advantages, MNC price/quality product strategies, and firm performance? A cross-national contingency framework is developed, identifying three “regional stereotypes” of price/quality relationships, fueled by history and consumer perceptions, which appear to result in superior MNC performance. Findings indicate that the “stereotypes'” influences have diminished over time (as MNCs shift from home country advantages to global firm-specific advantages). However, Triad MNCs that use these product strategies (Japan [superior value], EU [premium] and U.S. [economy]) still, on average, demonstrate superior performance.